Bell Shape Curves of Hemolysis Induced by Silver Nanoparticles: Review and Experimental Assay - Roberto Luna-Vázquez-Gómez; María Evarista Arellano-García; Yanis Toledano-Magaña; Juan Carlos García-Ramos; Patricia Radilla-Chávez; David Sergio Salas-Vargas; Francisco Casillas-Figueroa; Balam Ruiz-Ruiz; Alexey Pestryakov; Nina Bogdanchikova (Nanomaterials, 2022)
The hemolytic activity assay is a versatile tool for fast primary toxicity studies. This work presents a systematic study of the hemolytic properties of ArgovitTM silver nanoparticles (AgNPs) extensively studied for biomedical applications. The results revealed an unusual and unexpected bell-shaped hemolysis curve for human healthy and diabetic donor erythrocytes. With the decrease of pH from 7.4 and 6.8 to 5.6, the hemolysis profiles for AgNPs and AgNO3 changed dramatically. For AgNPs, the bell shape changed to a step shape with a subsequent sharp increase, and for AgNO3 it changed to a gradual increase. Explanations of these changes based on the aggregation of AgNPs due to the increase of proton concentration were suggested. Hemolysis of diabetic donor erythrocytes was slightly higher than that of healthy donor erythrocytes. The meta-analysis revealed that for only one AgNPs formulation (out of 48), a bell-shaped hemolysis profile was reported, but not discussed. This scarcity of data was explained by the dominant goal of studies consisting in achieving clinically significant hemolysis of 5–10%. Considering that hemolysis profiles may be bell-shaped, it is recommended to avoid extrapolations and to perform measurements in a wide concentration interval in hemolysis assays.